Pasifika women's knowledge and perceptions of cervical-cancer screening and the implementation of self-testing in Aotearoa New Zealand: A qualitative study - Naomi Brewer; Sunia Foliaki; Michelle Gray; John D. Potter; Jeroen Douwes (Elsevier, 2022)
Summary: Background: In Aotearoa New Zealand, Pasifika women have a higher rate of cervical cancer incidence and mortality than European/Other women and a lower screening rate. Despite actions to reduce the barriers, there has been little change in screening coverage for Pasifika women since 2007. Novel strategies are therefore required. Persistent cervical infection with oncogenic human papillomavirus (HPV) causes virtually all cervical cancers and HPV testing will be implemented in Aotearoa in 2023, with women being able to choose to self-test. We undertook a qualitative focus group (FG) study with Pasifika women to explore their perspectives on the barriers to, and facilitators of, HPV self-testing and how best to implement this in Aotearoa. Methods: A trained female Pasifika Research Assistant facilitated participant recruitment and the FGs. Eligible participants self-identified as Pasifika, were aged 30-69 years, in the Wellington area, who had never been screened or who were overdue (≥5 years) for cervical-cancer screening. Recruitment was predominantly through Pasifika key-informant networks and in collaboration with Pasifika primary care providers. Participants were offered face-to-face FGs but, due to occasional Covid-19 restrictions and personal preferences, FGs via Zoom were also used. The FGs were audio-recorded and transcribed verbatim. The FG transcripts were thematically analysed. Findings: Seven FGs were conducted with 24 participants. We identified five main themes around barriers and potential facilitators of HPV self-testing in Pasifika women: 1) perceptions and knowledge of cervical-cancer screening; 2) challenges to engaging in organised cervical screening; 3) perceptions of self-testing for HPV and challenges women face when deciding to self-test; 4) enthusiasm for an HPV self-test; and 5) information and communication. Knowledge about cervical cancer and screening varied considerably among participants, with some never having heard about cervical-cancer screening. The main challenges that were raised were personal privacy and confidentiality and time management. There was consensus around the need for adequate, consistent, and accurate accessible information to boost the confidence of women undertaking self-testing. In general, the participants were eager for self-testing to be made available soon. This was accompanied by the need for the promotion and implementation of self-testing to include a collective/community approach consistent with Pasifika worldviews. Interpretation: Although participants were enthusiastic about HPV self-testing, multi-level and interacting barriers exist to participation by Pasifika women in HPV self-testing. Implementation of self-testing in Aotearoa New Zealand should be accompanied by clear information about the entire process, using culturally appropriate tailored educational campaigns in different Pasifika languages. Funding: The study was supported by the Collaboration for Cancer Research Aotearoa New Zealand (CCR).